SISTEM INFORMASI PANTI ASUHAN HARAPAN BANGSA REMBANG BERBASIS WEB (Information Technology and Telematics, 2014)
Dwi Priantoko Abstract –This final project examines the making of a web-based information system that contains information about the Nation of Hope orphanage town Apex. The problem is how to design and build a web-based information system that will be able to provide information about the orphanage and make it easier for donors to make a donation without having to come to the orphanage. System development method used is a prototype model. The software implementation is used Dreamweaver, Photoshop with PHP and MySql. Of this thesis has produced an information system application promotion Nations Hope orphanage Apex web-based which can be used by the home keepers to better provide complete information to prospective donors, especially the wider community or the other. For the improvement of the design can be improved more modern look and additional information such as a list of foster children and donors. Keywords: Rembang, Web, Panti Asuhan, Sistem Informasi